Evaluation of anti-tetanus IgG antibody levels and influencing factors in patients undergoing hemodialysis - Özsoy, Metin; Öztürk, Hakkı; Tuna, Ayşegül; Varlıbaş, Artuner; Cesur, Salih; Aksoy, Altan; Çifci, Aydın; Demir, Mehmet Emin (Frontiers in Immunology, 2025)
AimThis study aimed to assess anti-tetanus IgG antibody levels and identify determinants of inadequate tetanus immunity among maintenance hemodialysis (HD) patients.MethodsIn this cross-sectional study, anti-tetanus IgG levels were measured by quantitative ELISA in 162 adult HD patients from two dialysis centers in Ankara, Turkey. Protective immunity was evaluated using both international (≥ 0.1 IU/mL) and robust (≥ 0.5 IU/mL) cut-offs. Demographic and clinical factors associated with immunity were analyzed by multivariate logistic regression.ResultsOnly 16.7% of HD patients achieved robust protection (≥ 0.5 IU/mL), whereas 49.8% had minimal protection (≥ 0.1 IU/mL). Protective immunity was independently associated with younger age (OR 1.07 per year; p = 0.004), shorter dialysis duration (OR 1.07; p = 0.030), male sex (female OR 2.92; p = 0.048), and recent booster vaccination within 10 years (OR 0.11; p < 0.001). Diabetes mellitus was not an independent factor.ConclusionMost HD patients lacked durable tetanus immunity, particularly older females on long-term dialysis. The findings highlight the need for regular antibody monitoring, early revaccination, and structured booster programs to maintain adequate protection in this high-risk population.